2005
DOI: 10.1074/jbc.m408143200
|View full text |Cite
|
Sign up to set email alerts
|

Menin Suppresses Osteoblast Differentiation by Antagonizing the AP-1 Factor, JunD

Abstract: Mice null for menin, the product of the multiple endocrine neoplasia type 1 (MEN1) gene, exhibit cranial and facial hypoplasia suggesting a role for menin in bone formation. We have shown previously that menin is required for the commitment of multipotential mesenchymal stem cells into the osteoblast lineage in part by interacting with the bone morphogenetic protein (BMP)-2 signaling molecules Smad1/5, and the key osteoblast transcriptional regulator, Runx2 (Sowa H., Kaji, H., Hendy, G. N., Canaff, L., Komori,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
0
41
1
4
Order By: Relevance
“…These results suggest that JunD and menin generally function in combination when they exert their biological effects in vivo. A recent study demonstrated that this is the case in bone development, wherein menin and JunD function as a complex in the regulation of osteoblast differentiation (Naito et al 2005). The present results of ours have reinforced this notion.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that JunD and menin generally function in combination when they exert their biological effects in vivo. A recent study demonstrated that this is the case in bone development, wherein menin and JunD function as a complex in the regulation of osteoblast differentiation (Naito et al 2005). The present results of ours have reinforced this notion.…”
Section: Discussionmentioning
confidence: 99%
“…JunD is coexpressed at high levels with Fra-2 in fully differentiated osteoblasts (McCabe et al, 1996). Loss of function of the negative JunD regulator, MEN1, correlates with increased JunD expression in osteoblasts and upregulation of osteoblast markers Naito et al, 2005). A clue that JunD acts after the commitment of the cells to the osteoblast lineage is the observation that JunD regulates critical osteoblast genes, although junDÀ/À mice have not been reported to demonstrate severe skeletal deformities characteristic of other osteoblast lineage genes.…”
Section: Jund Negatively Regulates Ras-mediated Transformationmentioning
confidence: 99%
“…The regulatory domain motif is well conserved in c-Jun and JunB, and was determined to have a negative effect on transcription (Kim et al, 2002). Downregulation of MEN1 in osteoblasts increases JunD transcriptional activity via the junD transcription autoregulatory loop, which in turn increases steady-state JunD protein level (Naito et al, 2005). Since MEN1 interaction is mediated by the JunD N-terminus, DJunD does not bind MEN1 and is not susceptible to MEN1 repression (Yazgan and Pfarr, 2002).…”
Section: Men1 Represses Jund Activity By Two Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations